Prolonged QTc interval predicts long-term mortality in cirrhosis: a propensity score matching analysis. (4th May 2021) - Li, Shuhong; Hao, Xuwen; Liu, Simiao; Gong, Yanxia; Niu, Wei; Tang, Yanping
Abstract: Background: Prolonged corrected QT (QTc) interval is a hallmark of cirrhotic cardiomyopathy (CCM) and has been ascertained to predict mortality in cirrhosis. However, some critical issues remain to be addressed including unanimous cut-off, calculation approach and applicable population. Methods: A total of 274 patients with cirrhosis were included. The prolonged QTc interval over 440 ms according to adjusted Fridericia's formula was used to stratify enrolled subjects. Independent predictors of 3-year mortality were identified with Cox regression model. The Kaplan–Meier method was implemented to obtain survival curves. To reduce impact of selection bias and possible confounders, a propensity score matching (PSM) analysis was used. Results: QTc > 440 ms was an independent risk factor in the entire cohort and PSM subset (HR 2.532, 95% CI 1.431–4.480, p =.001; HR 2.802, 95% CI 1.171–6.701, p =.021, respectively). Subgroup analysis showed that QTc > 440 ms was an independent predictor in cirrhotics with age ≤60 years (HR = 1.02, p =.035) and in the presence of ascites (HR = 1.01, p =.008). Conclusions: The prolonged QTc interval might help to identify patients with high-risk of all-cause mortality.